Studi Kualitatif Persepsi Masyarakat Desa Tentang Program Perencanaan Persalinan dan Pencegahan Komplikasi (P4K) - Shindy W. Ayu; Dwi B. Izzati; Atikah Atikah (SEAJOM: The Southeast Asia Journal of Midwifery, 2018)
P4K is one of the government's efforts to reduce Maternal Mortality Rate (MMR). The problem found was low community participation in P4K. This study aims to find out how people's perceptions about birth planning and complications prevention (P4K) programs. Method: This research is a qualitative study using purposive sampling technique in selecting samples. The samples used were 21 people who had met the sample criteria. Data was collected through in-depth interviews and FGD (Focus Group Discussion). Data were analyzed through several stages namely data reduction, data transcripts, data presentation, coding, categorization and conclusions. Results: 1) Most of the P4K information obtained by respondents was considered to be lacking. 2) Respondents' perception of the implementation of P4K revealed that the program had not yet reached the target. 3) The majority of respondents perceive the distribution of P4K stickers among mothers as uneven and the majority of pregnant women have a perception that the activity has no benefit for themselves.4) Respondents are more dominant in the perception of village ambulances as four-wheeled motor vehicles as usual ambulances. 5) P4K supporting facilities in the village are not yet available namely dasolin / tabulin and blood donor management. Conclusion: the perception of the village community about P4K so far both about information about the program and its implementation is still considered to be less than optimal, because socialization is not carried out thoroughly to the community. Therefore, there is a need for good collaboration between community sectors, health institutions and village governments